A One-Step Electropolymerized Biomimetic Polypyrrole Membrane-Based Electrochemical Sensor for Selective Detection of Valproate - Yuan, Yuyang; Li, Tianyu; Ye, Zhichao; Feng, Yuyao; Chen, Zhe; Wang, Yusen; Sun, Yiqiao; Wu, Haoyu; Yang, Zhaodong; Wang, Yifan; Zhang, Yiran; Huang, Liquan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Bipolar disorder is a chronic mental disease with heavy social and economic burden that causes extreme mood swings on patients. Valproate is a first-line drug for bipolar disorder patients to stabilize their daily mood. However, excessive drug concentrations in the blood can induce severe adverse effects, which necessitate the monitoring of blood valproate levels for patients. Here, we developed an innovative biochemical sensor for selective and simple detection of valproate based on a molecularly imprinted polymer membrane via one-step electropolymerization. Gold nanoparticles were electrochemically modified to the screen-printed electrode under the selective membrane to enhance its conductivity and stability. The successfully fabricated biosensor was characterized by scanning electron microscopy, cyclic voltammetry and differential pulse voltammetry methods. Binding of the target molecules to the valproate-customized biomimetic polypyrrole membrane blocks cavities in the membrane and alters its electric properties, which can be detected as a decrease in the peak current by differential pulse voltammetry methods. The peak current change presents a great log-linear response to the valproate concentration around the therapeutic window. The detection limit of this method was 17.48 μM (LOD, S/N=3) and the sensitivity was 31.86 μM/μA. Furthermore, the biosensors exhibited both satisfying specificity with the interference of other psychological pharmaceutical drugs and uniformity among sensors, indicating their potential and reliability in translational application. This simple and reliable method of sensing valproate molecules not only provides an exceptional solution to valproate point-of-care testing in clinical, but also has a broad prospect for the development of biosensors determining other small molecules with chemical inertness.